The Maritime World of Early Modern Britain - Davey, James (Lecturer in naval and maritime history); Blakemore, Richard, 1987- (Maritime humanities, 1400-1800., 2020)
Britain's emergence as one of Europe's major maritime powers has all too frequently been subsumed by nationalistic narratives that focus on operations and technology. This volume, by contrast, offers a daring new take on Britain's maritime past. It brings together scholars from a range of disciplines to explore the manifold ways in which the sea shaped British history, demonstrating the number of approaches that now have a stake in defining the discipline of maritime history. The chapters analyse the economic, social, and cultural contexts in which English maritime endeavour existed, as well as discussing representations of the sea. The contributors show how people from across the British Isles increasingly engaged with the maritime world, whether through their own lived experiences or through material culture. The volume also includes essays that investigate encounters between English voyagers and indigenous peoples in Africa, and the intellectual foundations of imperial ambition.